“Healthy” quality of seniors life – a challenge for health promotion - Dworak, Alina (Old Age in the Stream of Life: Reflections on Old Age. Volume 2, 2019)
Demographic aging of the population, expressed by the increase in the society percentage of elderly people is a social process, which is in the interest of researchers in many fields both medicine, public health, psychology, sociology or social policy. Reason of the increase in the society percent of older people is the extending the duration of human life with a simulta neous decrease in the number of births. Demographic aging of the Polish population, proceed in a similar manner to most European societies. Senile changes are manifested with varying intensity in different periods of human life, causing a progressive reduction of self-reliance, often helplessness. The process of population aging is a problem all over the world, and lengthening the duration of life is not always associated with its quality. Assessing the quality of life of older people we should take into account aspects related to the health and well-being, as well as exponents of social functioning. Reaching old age in good health requires the targeting of social policy not only to extend life, but also to improve its quality. It is also a task for the health promotion of older people, which is the process towards both to change the style of life of older people, as well as changes in the organization of health care and social assistance for the elderly, and to improve the quality of life in the “joy of life”.